Gastrointestinal Symptoms in Lysosmal Disease - IMANZADEH, Farid (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Imanzadeh F. Gastrointestinal Symptoms in Lysosmal Disease. Iran J Child Neurol Autumn 2012; 6:4 (suppl. 1):17-18. pls see PDF. References: 1. Semenza GL, Pyeritz RE. Respiratory complications of mucopolysaccharide storage disorders. Medicine (Baltimore) 1988; 67:209. 2. Wraith JE, Scarpa M, Beck M, et al. Mucopolysaccharidosis type II (Hunter syndrome): a clinical review and recommendations for treatment in the era of enzyme replacement therapy. Eur J Pediatr 2008; 167:267. 3. Stevens JM, Kendall BE, Crockard HA, Ransford A. The odontoid process in Morquio-Brailsford’s disease. The effects of occipitocervical fusion. J Bone Joint Surg Br 1991; 73:851. 4. Jones AE, Croley TF. Morquio syndrome and anesthesia. Anesthesiology 1979; 51:261. 5. Ashraf J, Crockard HA, Ransford AO, Stevens JM. Transoral decompression and posterior stabilisation in Morquio’s disease. Arch Dis Child 1991; 66:1318. 6. Neufeld EF, Muenzer J. The metabolic and molecular bases of inherited disease, Scriver C, Beaudet AL, Valle D, Sly W (Eds), McGraw- Hill, New York 2001. p.3421. 7. Wraith JE. The mucopolysaccharidoses: a clinical review and guide to management. Arch Dis Child 1995; 72:263. 8. Cleary MA, Wraith JE. The presenting features of mucopolysaccharidosis type IH (Hurler syndrome). Acta Paediatr 1995; 84:337. 9. Elsner B. Ultrastructure of the rectal wall in Hunter’s syndrome. Gastroenterology 1970; 58:856. 10. Cleary MA, Wraith JE. Management of mucopolysaccharidosis type III. Arch Dis Child 1993; 69:403.